1991
DOI: 10.1002/art.1780340302
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic symptoms and human immunodeficiency virus infection. The influence of clinical and laboratory variables in a longitudinal cohort study

Abstract: The present study was designed to prospectively evaluate the frequency of rheumatic symptoms in a cohort of patients infected with the human immunodeficiency virus (HIV), to examine the relationship between such findings and a variety of clinical and epidemiologic variables, and to evaluate the impact of rheumatic symptoms on the natural history of the HIV infection. One hundred seventeen patients were evaluated over a mean of 24.6 months (range 0.5–85 months). Cumulatively, 1.7% had Reiter's syndrome, 1.7% ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 14 publications
(5 reference statements)
1
20
0
1
Order By: Relevance
“…Thus, the FIV-induced immunological disease is paradoxical since the hyperimmunoactive state occurs shortly before or concurrently with the severe immunode®ciency syndrome in the infected animals. This presentation of the immune disorders closely resembles the presentation in human AIDS (Calabrese et al, 1991).…”
Section: Pathogenesis and Infectionsupporting
confidence: 53%
“…Thus, the FIV-induced immunological disease is paradoxical since the hyperimmunoactive state occurs shortly before or concurrently with the severe immunode®ciency syndrome in the infected animals. This presentation of the immune disorders closely resembles the presentation in human AIDS (Calabrese et al, 1991).…”
Section: Pathogenesis and Infectionsupporting
confidence: 53%
“…No previous prospective studies of the incidence and prevalence of septic arthritis in HIV-infected individuals are available, but several studies suggest that this combination is infrequent. In a longitudinal cohort study of 117 HIV-1-seropositive patients followed up over a mean period of 24.6 months, Calabrese et al [7] reported one case of SA. Moreover, Solinger and Hess [8] did not find a single case among 1100 HIV-seropositive out-patients.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of rheumatological syndromes in HIV patients varies from less than 1% to 60% [2,[5][6][7]. The list of reported autoimmune diseases in HIV/AIDS is found in Table 2.…”
Section: Infectionmentioning
confidence: 99%